Crop Diseases - Tripathi, D.P; Tripathi, D.P (Ludhiana Kalyani)
This book described diseases of plant along with the information on disease epidemology, symptomology, nature, morphology and pathogenic effects of different pathogens responsible for causation of diseases.
Chlorosis Phyllody Scab
Keywords: Chlorosis, Phyllody, Scab